GREEN BUILDING IN ACHIEVING SUSTAINABLE REGIONAL DEVELOPMENT - Danyliuk , M.M.; Dmytryshyn , M.V. (The actual problems of regional economy development, 2020)
The purpose of this research is to identify the key characteristics of green building that are necessary for the possible benefits and prospects. Research methods used in the article - comparison, analogy, induction and deduction, systems analysis and systems approach. Results. The article reveals the key characteristics, needs and prerequisites for the existence of green building. The difference between traditional and green construction is revealed. The place of green construction as a part of green economy is characterized. The factors by which green construction objects affect the environment and public health are singled out; they are also structured in a logical sequence of appearance. Green certification systems have been studied. The LEED standard, which is used in the construction of new and renovation projects; interior reconstruction and decoration of buildings in operation; residential real estate; suburban housing and cottage settlements, is characterized. The BREEAM standard is similarly described as one of the most well-known and widespread methods of assessing the environmental performance of buildings (office centers, shopping malls, industrial facilities, secondary schools, apartment buildings, courts and prisons, available housing). The indicators of the standards (place to build, water and energy efficiency, consumption of materials and resources, environmental quality, innovation, management, health, transport, waste disposal, pollution) are evaluated and their rating in the scoring system is fixed. Factors for increasing the investment attractiveness of green construction projects have been identified. A schematic model of increasing the investment attractiveness of green construction through taking into account the factors of influence (uniqueness, quality, responsibility) and benefits (reducing costs and increasing opportunities) has been developed and described. The benefits of green building for four actors: region, investors, construction companies and owners of «green» buildings are outlined. Scientific originality. The result of the publication is the construction of a holistic description of green building, starting from the preconditions and needs of its existence, and ending with the benefits and prospects. The practical significance of the results. The results are properly described and graphically represented; this allows them to be used in the process of further scientific research, practical activities and to replenish the intellectual capital of all interested readers.